The impact of feasibility and meaningfulness of ESD activities on sustainability awareness in Japanese community learning centers - Khalaf Mohamed Abdellatif (Education and Development Research, 2025)
Although feasibility (practical accessibility) and meaningfulness (personal relevance) are established drivers of participation in non-formal education, their direct impact on learning outcomes, specifically sustainability awareness within Japanese Community Learning Centers (CLCs), has not been empirically established. This research addresses this research gap by examining how perceived feasibility and meaningfulness of Education for Sustainable Development (ESD) activities affect sustainability awareness among participants in CLC in Japan. Using a mixed-methods case study approach, quantitative data were collected from 370 participants at Misonou Community Center in Hiroshima and analyzed through structural equation modeling (SEM), complemented by qualitative insights from 30 follow-up interviews. Results indicated that both feasibility (β = 0.32, p < .001) and meaningfulness (β = 0.48, p < .001) significantly predicted sustainability awareness, collectively explaining 56% of variance, with meaningfulness showing stronger predictive power. These findings provide an empirically validated framework for ESD program design, suggesting that practitioners should adopt a dual-focused strategy that reduces logistical barriers while collaboratively developing curricula that reflect local contexts and participant values. This evidence-based approach enables CLCs to effectively support national sustainability objectives and promote environmental consciousness.